Aspek Mikrobiologi Dendeng Asap Dengan Daging yang Berbeda pada Pengasapan Tempurung Kelapa - Jahidin, Jaya Putra (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2014)
Â The objective of this experiment was to study the characteristics of beef and buffalo meat as raw materials of smoked dendeng and the use of coconut shell. Parameters observed during research were microbiology variables (total plate count, S. aureus, molds). This study was designed using the design of complete randomized design (CRD) with three replications. Nonparametric data of organoleptic tests processed statistically by Kruskal-Wallis method. Parametric data physical, chemical and microbiological variable analyzed by t test (Steel and Torrie 1993). Data processing using the program Statistical Analysis System (SAS) 9.1 and Minitab 15 version. The results of this study indicate that microbiological characteristics of dendeng batokok in this research in general is still quite good until 7 days of storage. Â Key words: dendeng batokok, type of meat, coconut shell, characteristic.